Reliability-based design of reinforced concrete pipes to satisfy the TEBT - de Sousa, Alex Micael Dantas; Prado, Lisiane Pereira [UNESP]; Debs, Mounir Khalil El (FapUNIFESP (SciELO), 2023)
Reinforced concrete pipes are usually designed to attend a three-edged-bearing test (TEBT) using the partial safety factors from building structures. This study presents an alternative approach to designing RC pipes based on simplified reliability analyses. The procedure consists of providing curves of failure probability according to the reinforcement areas used in the pipes. The results indicate that RC pipes with simple reinforcement show a failure probability of around 1% with the most traditional design method, even using the partial safety factors from buildings, due to the higher dispersion of the concrete cover and the use of a single reinforcement layer to satisfy different control sections. Meanwhile, RC pipes with double reinforcement show a significantly lower failure probability as each reinforcement layer is designed to satisfy the bending moments from different control sections and due to the larger pipe thickness. In summary, the large randomness of the reinforcement position increases the failure probability of these members compared to traditional building structures.
Keywords: failure probability; reinforced concrete pipes; reliability-based design; three-edge-bearing test